Amnestic syndrome in the course of seronegative limbic encephalitis complicated by drug-resistant epilepsy: a case report - Łoś, Kacper; Kulikowska, Joanna; Chorąży, Monika; Kułakowska, Alina; Waszkiewicz, Napoleon; Galińska-Skok, Beata (Frontiers in Immunology, 2024)
We present the case of a 35-year-old female patient admitted to the hospital with symptoms of rapidly increasing disturbances of consciousness and fever for 48 hours. A lumbar puncture, bacteriological and virological examinations, as well as initial imaging studies, did not show abnormalities. Brain magnetic resonance imaging (MRI), repeated several times, showed hyperintense confluent lesions in both temporal lobes and atrophy of both hippocampus. General examination, cerebrospinal fluid culture, the panel of antineuronal antibodies, and tumor markers remained negative on subsequent repeats. Despite several laboratory and imaging studies, the etiology of the disease could not be established, infections were excluded, and no autoantibodies were found. A diagnosis of probable limbic encephalitis, amnestic syndrome resulting from organic brain damage, and drug-resistant epilepsy was made. The patient, with limbic encephalitis complicated by drug-resistant status epilepticus, was treated with cycles of immunoglobulin and subsequent plasmapheresis. Then she was transferred to the Department of Psychiatry for diagnosis and treatment of intermittent psychotic disorders. During hospitalization, the patient was observed to have multiple epileptic seizures with temporal and frontal morphology, amnestic syndrome covered with confabulations, and periodic psychotic disorders with the occurrence of visual hallucinations. Antiepileptic treatment was escalated by including cenobamate in increasing doses. To control mental disorders, duloxetine, tiapride, and cognitive function exercises were introduced. There was a slight improvement in memory, the cessation of confabulations, and the emergence of the patient's criticism of the symptoms presented. Psychotic symptoms have subsided, and the number of epileptic seizures decreased. The described case portrays a unique coincidence of disease symptoms difficult to treat. It points out the therapeutic difficulties that can occur in patients with suspected autoimmune encephalitis. What is more, it points out the need for multispecialty care of a patient with psychotic symptoms in the course of epilepsy accompanied by amnestic syndrome.